Enhancing socio-emotional learning and mental health through computational thinking: a cross-cultural analysis of the COMPUSEL programme - Adelinda Candeias; Adriana Felix; Anisoara Dumitrache; Beatrice Almășan; Ilke Evin Gencel; Magdalena Zadworna; Karolina Kossakowska; Angeliki Sakellariou; Miltos Sakellariou; Cavus Sahin; Cigdem Sahin Taskin (Frontiers in Psychology)
PurposeThe COMPUSEL curriculum is designed to enhance primary school students’ five core Socio-emotional (SEL) competencies (self-awareness, self-management, social awareness, relationship skills, and responsible decision-making) and mental health by incorporating computational thinking. This study evaluates the curriculum’s impact across five European countries (Greece, Poland, Portugal, Romania, and Turkey), analyzing cultural differences in its implementation.MethodologyA quasi-experimental research design was employed to examine the curriculum’s impact. The piloting process included a training seminar for teachers, after which a volunteer teacher was selected to implement the curriculum. The curriculum featured digital stories and a comprehensive guide for teachers, which outlines the COMPUSEL learning model and provides guidance for effective implementation. Data were collected from 113 students through pre-test and post-test evaluations, without the use of a control group.FindingsThe findings revealed statistically significant differences across all dimensions in Greece, Turkey, and Poland. In Portugal, significant differences were noted in four dimensions, with the exception of responsible decision-making. Conversely, no statistically significant differences were observed in any dimension in Romania.ConclusionThe COMPUSEL project’s curriculum is designed to streamline planning and offer flexible models that promote sustainable education, catering to diverse student needs. By integrating digital storytelling and computational thinking into SEL, the curriculum provides a holistic approach that equips students with essential 21st-century life skills. The study also highlighted the varied cultural effects on the curriculum’s implementation across different countries. These cultural variations may have influenced the demonstration of the curriculum’s overall effectiveness, yet the research confirms that the COMPUSEL curriculum is effective in most participating countries.